2018
DOI: 10.4274/tjps.24381
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Deuterium-Depleted Water plus Rosa damascene Mill. Essential Oil via Cyclooxygenase-2 Pathway in Rats

Abstract: Objectives: Natural medicine has been proposed in treating of sepsis in the worldwide. So, in this study, the effect of deuterium-depleted water (DDW) alone and adjuvant with Rosa damascene Mill. essential oils (RD) was considered through the evaluation of oxidative stress/antioxidant parameters and the expression of cyclooxygenase-2 (COX-2) inflammatory gene in liver damage caused by sepsis. Materials and Methods: The rats were randomly divided into 5 groups: 1) laparotomy (LAP) group; 2) cecal ligation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…*These data are presented here in order to make a new compression among treatment groups (Fatemi et al. 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…*These data are presented here in order to make a new compression among treatment groups (Fatemi et al. 2019).…”
Section: Resultsmentioning
confidence: 99%
“…c p < 0.05 is considered significantly between *DDWs treatment groups with DDW+ML groups *These data are presented here in order to make a new comparison among treatment groups (Fatemi et al. 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The isotopes of certain biogenic elements of a non-radioactive nature (Figure 2) such as hydrogen ( 1 H and 2 H), oxygen ( 16 O, 17 O, 18 O), carbon ( 12 С, 13 С) and nitrogen ( 14 N, 15 N); they cause a series of effects on the biochemical reactions and physiological processes of the organism, with a prominent influence on growth and development in both unicellular and multicellular organisms, as well as influencing energy metabolism and metabolic rate [3]. These reactions can affect the cell cycle and cell proliferation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Results of clinical trials have shown that R. damascena EO has tranquilizing effects without any serious complications [14][15][16]. Various reports also demonstrated its biological activities including antioxidant [17,18], anti-cancer [19], anti-inflammatory [20], anti-HIV [21,22], antifungal, antibacterial, and antimicrobial [16,[23][24][25] properties.…”
Section: Introductionmentioning
confidence: 99%